Analisis Fenomenologi Perhiasan bagi Perempuan Urban Jakarta - Dhyani Widiyanti (JURNAL RUPA, 2024)
Urban women and jewelry may be considered inseparable entities. Employing a phenomenological approach, this study interviewed three urban women as informants to construct meaning linking jewelry ownership, urban culture as elucidated by Keith (2003), and cultural hybridity according to Tuncer's perspective (2023). The findings of this research indicate that urban women in Jakarta engage in cultural practices through activities associated with collectivity, message conveyance, connectivity, and socially replicable patterns, while also being integral parts of urban culture with activities emphasizing fashion and social norms. Additionally, urban women in Jakarta exhibit social hybridity through intercultural interactions that yield innovative ideas in jewelry making. The intercultural interactions in question involve various endeavors, including preserving cultural heritage, conveying messages through expression, sustaining within communities, serving as a means of psychological healing, and aspiring to make their designed jewelry products inspirational to many.